E-LEARNING DURING THE PANDEMIC: LOOKING FOR AN IDEAL E-LEARNING PLATFORM A survey to English teachers of vocational schools in Majalengka and Indramayu Regency (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2021)
This paper reports on finding of research results to English teachers of vocational school in Majalengka and Indramayu districts regarding the learning platforms they used on teaching and learning activities during the pandemic. A total of 31 teachers participated in this study. Data obtained from survey results using google form by open and closed questions. The results stated that 71% of participants using google classroom, but only 29% actually used google classroom. The remaining 42% combines google classrooms with Edmodo, WhatsApp, Zoom, Google Meet, email, google forms, google drive, Schoology and also LMS which is developed in their schools. 54% of respondents stated that they used more than two kinds e-learning platforms to carry out teaching and learning activities on their English class, and even, some of them use 4 or 5 e-learning platforms at once. 64.5% of respondents said the e-learning platform they were using was not ideal so they used a lot of e-learning platforms at once although it is inefficient ways. 83.9% said they were still looking for the ideal e-learning platform and 100% said they need for training on e-learning platforms so that they could choose the best one to apply in their class.